PENGARUH MODEL PEMBELAJARAN SOMATIC, AUDIOTORY, VISUALIZATION, DAN INTELLECTUAL (SAVI) TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS V UPT SPF SD INPRES PARANG KOTA MAKASSAR - Noormina; Sari Achmad, Widya Karmila; Salam, Rosdiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the phenomenon of low English vocabulary mastery and similar problems found at the UPT SPF SD Inpres Parang. The objectives of this study were to determine (1) the description of the application of the SAVI learning model in fifth-grade English lessons, (2) the description of students' vocabulary mastery, and (3) the effect of the SAVI model on students' English vocabulary mastery. This research is a Quasi Experimental Design with a Nonequivalent Control Group Design. The research population includes all 30 fifth-grade students, with class VB as the experimental group and class VA as the control group, each consisting of 15 students. Data collection techniques include tests and observations. The results showed that the implementation of the SAVI model was very successful. The average score of the experimental class increased from adequate in the pretest to excellent in the posttest. Improvements were also seen in the indicators of the ability to use vocabulary in the correct context, spell correctly, and translate vocabulary according to its meaning. The results of the independent t-test showed a significance value of < 0.001 (< 0.05), so the alternative hypothesis was accepted. Thus, there was a significant effect of the application of the SAVI learning model on the English vocabulary mastery of fifth grade students at UPT SPF SD Inpres Parang.